Data storage system for wireless sensor networks - Sacramento, David (2015)
Wireless sensor networks (WSNs) are starting to have a high impact on our societies and, for next generation WSNs to become more integrated with the Internet, researchers recently proposed to embed Internet Protocol (IP) v6 into such very constrained networks. Also, Constrained Application Protocol (CoAP) and Observe have been proposed for RESTful services to be provided. CoAP can be used not only between nodes on the same constrained network but also with other nodes in the Internet. The latter is possible if CoAP is translated to Hyper Text Transfer Protocol (HTTP). With CoAP/Observe, a client may store notifications in it and use a stored notification, as long as it is fresh, to serve other clients requesting it, without contacting the origin server. However, the use of CoAP/Observe for clients to be notified of resource changes, together with the possibility of incorporating proxies, raise optimization issues when multiple requests for observation are present in a network. These optimization issues involve registration steps, energy saving, consistency and caching. Registration steps must be carefully planned (which proxies to use), while keeping data consistency and timeliness, so that energy is saved. In this thesis, a careful planning of registration steps for data/notification storage is proposed. That is a framework for the planning of such registration steps, together with the aggregation and scheduling of notification deliveries at proxies, so that energy saving is maximized, bandwidth is used efficiently and the overall delay is reduced. This framework can be applied to different types of applications. A heuristic approach is also proposed for solutions to be obtained faster.